2020
DOI: 10.12982/cmujns.2020.0031
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Assessment of Total Bioactive Contents, Antioxidant, Anti-Alzheimer and Antidiabetic Activities of Leaves Extracts and Fractions of Aloe vera

Abstract: The present work was conducted to evaluate the quantitative analysis of the leaves of Aloe vera and to evaluate their potential antioxidant, anti-Alzheimer and antidiabetic properties in vitro. The acetone extract, methanolic extract and its four fractions were subjected to quantitative determination of polyphenol, flavonoid, flavonol, condensed tannin and hydrolysable tannin contents. Then, the antioxidant properties of all extracts and fractions were evaluated by using DPPH free radical scavenging, ABTS cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These findings can be explained by the existence of chemicals in the extracts that are responsible for the inhibition of the AChE [ 4 ] and particularly by the ethanolic extract’s flavonoids. Our results agree with those of the investigations conducted by Teyeb et al [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings can be explained by the existence of chemicals in the extracts that are responsible for the inhibition of the AChE [ 4 ] and particularly by the ethanolic extract’s flavonoids. Our results agree with those of the investigations conducted by Teyeb et al [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…These biomolecules have significant importance in reducing oxidative stress, which could destroy the biological mechanisms in the human body [ 3 ]. In reality, the preference for natural substances is also a consequence of the lack of adverse effects where numerous studies have shown that natural compounds counteract the negative effects of pharmaceutical treatments, implying that these natural molecules have greater medicinal value [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The chemical makeup of Aloe varies by species, climate, and growth conditions and some important phytochemicals reported in Aloe include alkaloids, flavonoids, saponins, terpenoids, glycosides, tannins, phenolic compounds, carbohydrates, protein, sterols, protein, tri-terpenoids, glucose, and galactose, etc. and some derivatives [17,[25][26][27]. Vitamins, enzymes, micro and macro minerals, sugars, anthraquinones, campesterol, sitosterol and lupeol, salicylic acid, and amino acids were also reported [28].…”
Section: The Phytochemistry and Biological Activities Of Different Pl...mentioning
confidence: 99%
“…A lot of studies have reported diverse classes of phytochemicals (Table 2) in Aloe species using different methods [17,[25][26][27][51][52][53][54][55][56][57][58]. Sathyaprabha et al [51] found tannins, saponins, terpenoids, flavonoids, steroids, cardiac glycosides, phlobatannins, squalene oleic acid and dodecanoic acid in A. vera.…”
Section: Phytochemistry Of a Veramentioning
confidence: 99%
“…Phenolic compounds are a main class of secondary metabolites in medicinal plants. The beneficial effects of phenolic compounds is attributed to the antioxidant activity that mainly due to the capacity of scavenging free radicals, donating hydrogen atoms, electrons, or chelate metal cations [Bendjedid, et al, 2020]. Gardenia carinata Wallich., belonging to the family Rubiaceae, is native from Malaysia and Indonesia and it has been found in the southern part of Thailand.…”
Section: Introductionmentioning
confidence: 99%